Discovery of Very High Energy gamma-Ray Emission from Centaurus a with H.E.S.S. - Aharonian, F.; Akhperjanian, A.; Anton, G.; De Almeida, U.; Bazer-Bachi, A.; Becherini, Y.; Behera, B.; Benbow, W.; Bernlöhr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Institute of Physics Publishing, 2009)
We report the discovery of faint very high energy (VHE; E > 100 GeV) gamma-ray emission from the radio galaxy Centaurus A in observations performed with the High Energy Stereoscopic System (H.E.S.S.) experiment, an imaging atmospheric Cherenkov telescope array consisting of four telescopes located in Namibia. Centaurus A has been observed for more than 120 hr. A signal with a statistical significance of 5.0sigma is detected from the region including the radio core and the inner kpc jets. The integral flux above an energy threshold of ~250 GeV is measured to be 0.8% of the flux of the Crab Nebula (apparent luminosity: L(>250 GeV) ˜2.6 × 1039 erg s-1, adopting a distance of 3.8 Mpc). The spectrum can be described by a power law with a photon index of 2.7 ± 0.5stat ± 0.2sys. No significant flux variability is detected in the data set. However, the low flux only allows detection of variability on the timescale of days to flux increments above a factor of ~15-20 (3sigma and 4sigma, respectively). The discovery of VHE gamma-ray emission from Centaurus A reveals particle acceleration in the source to >TeV energies and, together with M 87, establishes radio galaxies as a class of VHE emitters.